Determination of Essential Element and Titanium Contents in Rocks using Flame Atomic and Molecular Absorption Spectrometry - Le, Quang Huy; Nguyen, Thanh Nho; Bui, Trung Huu; Nguyen, Cong Hau; Le, Thi Anh Dao; Do, Huy Minh; Le, Thanh Long (Journal of Technical Education Science, 2022)
Rocks contain a large number of elements such as Na, K, Ca, Mg, Fe, Mn, and Ti. The determination of those element contents is important in geological and geographical exploration as well as the original identification and classification of rocks. Currently, the analysis of the elemental composition of rocks can be carried out on equipments such as ICP-OES, ICP-MS,... However, in some laboratories with limited conditions, the analysis has many difficulties. In the present study, we analyzed rock samples after being treated by microwave using flame atomic and molecular absorption spectroscopy. The results showed that the content of elements in the range of Na (0.31 – 2.46%), K (1.38 – 3.71%), Ca (0.08 – 0.23%), Mg (0.16 – 0.69%), Fe (2.38 – 5.19) %), Mn(0.08 – 0.1%) and Ti(0.12 – 0.36%). The study provides a simple and cost-effective method for rock analysis.